DIAGNOSIS OF CARDIAC COMPLICATIONS IN CHAGAS DISEASE - Fortunato, Nelice Cristina Gomes dos Santos; Araújo, Clayseane Nunes; Toledo, Rodolfo Ricardo; Alves, Alícya Freitas; Lamas, Matheus; Khaled, Saed Husein; de Oliveira, Rafael Augusto; Lino, Ana Luiza Leite; Mendes, Maisa Matos Maria (Seven Editora, 2026)
Introduction: Chagas disease is caused by the protozoan Trypanosoma cruzi and can be divided into two phases: the acute phase, which occurs soon after infection, and the chronic phase, which reveals signs and symptoms years after the first contact. Treatment with antiparasitic drugs has proven benefits in the initial phases; however, its effectiveness is limited in patients with established heart disease, in whom myocardial damage is largely irreversible. Thus, one of the most serious complications is chronic Chagas cardiomyopathy (CCC), characterized by progressive fibrosing inflammation, resulting in structural damage to the myocardium and the heart’s electrical conduction system. This process is often silent, hindering early diagnosis, worsening the patient’s clinical condition, and contributing to the high morbidity and mortality rate of Chagas disease. Methodology: This study is characterized as a narrative literature review. The data were consulted in scientific databases such as PubMed and SciELO, using the descriptors "Chagas disease", "Diagnosis" and "Chagas Cardiomyopathy", combined with the Boolean operator AND, according to the terminology of Medical Subject Headings (MeSH). The selection included guidelines from cardiology societies and articles published between 2020 and 2025, with full text available in Portuguese or English. Results: Imaging and laboratory tests are essential both for early diagnosis of chronic Chagas cardiomyopathy and for monitoring the patient’s health status. Electrocardiogram, echocardiogram, and the biomarkers BNP and NT-proBNP are considered the gold standard. Cardiac Magnetic Resonance Imaging and CRP also assist in the detailed investigation of this complication. Conclusion: Even in developed countries, underdiagnosis occurs or the condition is diagnosed as heart failure, especially in non-endemic areas. Therefore, diagnosing CCC depends on a proactive approach from the professional, since any sign of damage to the conduction system on the ECG or segmental alteration on the echocardiogram already classifies the patient as having heart disease, requiring more frequent clinical follow-up.